Obesity as a Predictor for Pulmonary Embolism and Performance of the Age-Adjusted D-Dimer Strategy in Obese Patients with Suspected Pulmonary Embolism - Gaugler, Jan O.; Righini, Marc; Robert-Ebadi, Helia; Sanchez, Olivier; Roy, Pierre-Marie; Verschuren, Franck; Miranda, Sebastien; Delluc, Aurélien; Le Gal, Grégoire; Tritschler, Tobias (Thrombosis and Haemostasis, 2023)
Introduction Obesity is a risk factor for venous thromboembolism, but studies evaluating its association with pulmonary embolism (PE) in patients with suspected PE are lacking.Objectives To evaluate whether body mass index (BMI) and obesity (i.e., BMI ≥30 kg/m2) are associated with confirmed PE in patients with suspected PE and to assess the efficiency and safety of the age-adjusted D-dimer strategy in obese patients.Methods We conducted a secondary analysis of a multinational, prospective study, in which patients with suspected PE were managed according to the age-adjusted D-dimer strategy and followed for 3 months. Outcomes were objectively confirmed PE at initial presentation, and efficiency and failure rate of the diagnostic strategy. Associations between BMI and obesity, and PE were examined using a log-binomial model that was adjusted for clinical probability and hypoxia.Results We included 1,593 patients (median age: 59 years; 56% women; 22% obese). BMI and obesity were not associated with confirmed PE. The use of the age-adjusted instead of the conventional D-dimer cut-off increased the proportion of obese patients in whom PE was considered ruled out without imaging from 28 to 38%. The 3-month failure rate in obese patients who were left untreated based on a negative age-adjusted D-dimer cut-off test was 0.0% (95% confidence interval: 0.0–2.9%).Conclusion BMI on a continuous linear scale and obesity were not predictors of confirmed PE among patients presenting with a clinical suspicion of PE. The age-adjusted D-dimer strategy appeared safe in ruling out PE in obese patients with suspected PE.
Keywords: clinical prediction; D-dimer; diagnosis; obesity; pulmonary embolism